Responsible Practice of Research: Safeguarding Research Integrity and Publication Ethics - Dhakal, Rebat Kumar (Journal of Education and Research, 2016)
In recent years, there has been an outburst of general interest on how we do ‘research’ (Bossi 2010; Lins & Carvalho, 2014) – right from planning to reporting results – and how we disseminate ‘knowledge’. This rise of interest has particularly resulted from the surfeit of news on dishonest practices of research community. Some of the ‘acts of wrongdoing’ or fraudulent research practices that arise in our academic debate comprise the cases such as creation of false data or manipulating data to generate preferred results, cheating or using other’s ideas as own, disclosing improperly the identity of participants, underserved authorship claims, submission to multiple journals, duplicate publications, salami slicing, and predatory publications. In fact, these practices pose a serious question on research integrity. But what actually is ‘integrity’ in research?